Online tools to support novice programming: A systematic review - Sim, Tze Ying *; Lau, Sian Lun * (2018)
Novice programming is a challenging subject to both the students and the educators. A novice programmer is required to acquire new knowledge to solve a problem and propose a solution systematically. This is followed by constructing the solution in a development environment that they are unfamiliar with. This research looks at the challenges faced by a novice programmer and the online methods that are popular to assist the students. Online block programming is a popular option. One of the software that had been implemented in the various research project is Scratch. From the reviewed research, it shows that the trend is moving towards an intelligent tutoring system, where students can have personalized engagement for their learning experience. This paper presents a systematic review conducted using the keywords ”novice programming”, ”introductory”, ”CS1”, ”difficulties”, ”challenges”, and ”threshold concepts”. From the review conducted, it is observed that most of the work is carried out to ease the implementation of the solution through an integrated development environment, and block programming. On the support for instructors, the discussion on curriculum and challenges in CS1 tops the chart. This is followed by active learning through online tools.